OPTIMASI WAKTU DAN SUHU FERMENTASI UNTUK MENINGKATKAN KUALITAS TEMPE DI DESA PADARINGAN KEC. PURWADADI KAB. CIAMIS JAWA BARAT - Sri Mardiyati; Pujiastuti Pujiastuti; Pandhu Pramarta; Edward Alfin (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2026)
This study investigates the optimization of fermentation time and temperature to improve tempe quality produced by household-scale artisans in Padaringan Village, Purwadadi District, Ciamis Regency, Indonesia. A descriptive qualitative approach was employed through direct observation over four consecutive days, with measurements recorded every three hours for temperature, relative humidity, and physical–sensory characteristics of tempe. The results demonstrate that fermentation follows a biological progression consisting of adaptation, active growth, optimal maturation, and degradation phases. During the first 24 hours, microbial adaptation and early mycelial growth occurred under temperatures of 27–32°C and humidity levels of 72–91%, producing soft texture and mild aroma. Optimal quality was achieved between 24–48 hours at stable temperatures of 27–29°C and humidity of 80–88%, characterized by uniform white mycelium, compact texture, and pleasant characteristic aroma. Beyond 48 hours, quality gradually declined as metabolic degradation intensified, indicated by texture softening, discoloration, and sharper odor. By 72–96 hours, tempe entered a post-optimal phase unsuitable for consumption. These findings confirm that fermentation duration is the most practical control factor for maintaining consistent quality in traditional production systems. Adjusting fermentation time according to environmental conditions provides an effective, low-cost strategy to enhance product quality, stability, and competitiveness among small-scale tempe producers.